A high-load dry composite positive electrode sheet and preparation method thereof

Through a multi-step method of high-speed mixing, low-temperature and low-speed mixing, prefibrosis and supersonic airflow crusher processing, combined with array through-hole coating aluminum foil current collector, the uneven dispersion of conductive agents and binders in the dry electrode process is solved. The problem of long electron ion transmission paths has realized the preparation of high-performance, high-load composite positive electrode sheets, improving electrochemical performance and energy density.

CN118841521BActive Publication Date: 2025-01-14SHENZHEN AUTOMOTIVE RES INST BEIJING INST OF TECH (SHENZHEN RES INST OF NAT ENG LAB FOR ELECTRIC VEHICLES)
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411279187.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-14
Estimated Expiration
2044-09-12

Smart Images

  • Figure CN118841521B_ABST
    Figure CN118841521B_ABST
Patent Text Reader

Abstract

The present application discloses a high-load dry composite positive electrode sheet and a preparation method thereof, which relates to the field of battery technology. A conductive carbon material with high conductivity and high aspect ratio and an oxide solid electrolyte with different particle sizes are introduced into the preparation material. The solid electrolyte is a mixed powder of nanoparticles and micron particles. The conductive agent, the solid electrolyte and the positive electrode active material are first mixed, and then the binder is mixed at a low speed under low temperature conditions. The mixed powder is then pre-fiberized and heat-insulated. After the heat insulation, the powder is treated with a supersonic airflow to fully fiberize the binder and uniformly disperse other component materials. Finally, the electrode membrane is formed by hot rolling, and the positive electrode sheet is obtained by rolling and compounding with a carbon-coated aluminum foil current collector with an array through-hole structure. The technical solution of the present application solves the problem of long electron and ion transmission paths and slow conduction in thick electrodes, improves the battery rate charge and discharge performance and the specific capacity of the active material, and improves the degree of fibrillation and material uniformity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of batteries, and in particular to a high-load dry composite positive electrode plate and a preparation method thereof. Background Art

[0002] Improving the energy density of liquid lithium-ion batteries is a key demand and important driving force for battery development. Batteries with higher energy density can store more energy in a smaller volume and weight, which not only reduces the overall weight of electric vehicles and improves their performance and handling, but also makes portable electronic devices lighter and enhances the user experience. In addition, improving energy density also helps to reduce the cost of batteries, because the cost per unit of energy decreases with the increase of energy density. Therefore, battery manufacturers and researchers are committed to continuously improving the energy density of liquid lithium-ion batteries by developing new battery materials and corresponding battery systems with higher specific capacity or voltage platforms, developing more advanced battery structure designs, and optimizing battery manufacturing processes.

[0003] In terms of optimizing battery structure design, such as developing high-load thick electrodes, ultra-thin diaphragms and current collector substrates, and more compact battery assembly technology, the overall energy density of the battery can be improved. The latter two are more difficult to achieve, and require accurate evaluation of the cost, overall safety and manufacturing process. On the whole, developing high-load thick electrodes and reducing the proportion of inactive components such as current collectors are the simplest and most effective ways to improve energy density. However, the increase in electrode thickness will lead to an increase in the transmission distance of ions and electrons, severe electrode polarization, and a significant reduction in electrochemical performance. Current research on thick electrodes focuses on the optimization of current collectors and coating processes. The increase in the amount of active material loading is achieved at the expense of a certain degree of sacrifice in electrode electrochemical performance or volume energy density. Therefore, to achieve an ideal thick electrode, the key issues of ion / electron transport in the electrode and the stacking density of active materials must be solved at the same time. In addition, due to the limitations of the wet process, cracking and stratification are prone to occur during the drying process. Therefore, the preparation of thick electrodes cannot be achieved through the wet coating process, and a new preparation process needs to be developed.

[0004] In recent years, solvent-free dry processes have been widely studied for the preparation of thick electrodes, which usually involve mixing the positive electrode active material, conductive agent and solid binder, fiberizing them, and then hot rolling them into a self-supporting film and then compounding them with the current collector. The dry positive electrode process can effectively control the electrode thickness and uniformity of thick electrodes, has unique advantages in the preparation of thick electrodes, and is suitable for the preparation of ultra-high loading electrodes. The dry positive electrode process is considered to be an important development direction in the field of lithium-ion battery manufacturing due to its advantages in improving battery performance, reducing costs and environmental friendliness.

[0005] CN116706074A is one of the technical solutions closest to the prior art, and relates to a dry electrode preparation method, a battery, and a dry electrode preparation device. This invention discloses a dry electrode preparation method, comprising: mixing and granulating a first conductive agent and a binder to obtain binder particles containing the first conductive agent; mixing the electrode material with the binder particles, and fiberizing the binder in the binder particles to obtain a mixture; compounding the mixture onto a current collector to obtain an electrode sheet. This invention solves the problem of uneven dispersion and insufficient fiberization of the first conductive agent and the binder in the prior art dry electrode preparation process.

[0006] CN117154005A is one of the technical solutions closest to the prior art, and relates to a dry electrode and its preparation method. This invention discloses a preparation method of a dry electrode, comprising the following steps: melting a first group of polytetrafluoroethylene, adding conductive nanoparticles to the melted first group of polytetrafluoroethylene, stirring, and sieving to obtain a glue solution; mixing active materials, a second group of polytetrafluoroethylene, an epoxy resin adhesive, and a conductive agent for fiberization to obtain a pretreated product; rolling the pretreated product to obtain a dry electrode film; spraying the glue solution on the surface of the current collector to form a conductive glue layer; adhering the dry electrode film to the outer surface of the conductive glue layer to obtain a dry electrode. The dry electrode of this invention has improved rate performance, a simple preparation method, and low raw material cost, and can be industrialized.

[0007] CN113871566B is one of the technical solutions closest to the prior art, and relates to a dry electrode membrane, its preparation method and application. The method described in this invention includes the following steps: 1) mixing the active material, the conductive agent and the polymer membrane evenly to obtain a mixture; 2) subjecting the above-mentioned mixed material to fiberization to obtain a mixture; 3) subjecting the obtained mixture to heating and calendering to prepare a dry electrode membrane. The method of this invention can greatly reduce the process difficulty of dry preparation of electrode sheets, has low requirements on the equipment used for fiberization, and has more complete fiberization and better dispersion uniformity between components.

[0008] CN112133923B is one of the technical solutions closest to the prior art, and relates to a positive electrode material layer suitable for a semi-solid battery, a preparation method thereof, a positive electrode sheet, and a semi-solid battery. The positive electrode material layer described in this invention includes: a network structure formed by overlapping polymer fibers, and positive electrode active materials, solid electrolytes, and polymer solid electrolytes dispersed and bonded to the network structure. In the positive electrode material layer of this invention, polymer fibers are used as binders to construct a network structure, and oxide solid electrolytes and polymer solid electrolytes have good ion conductivity. Dispersed in the network structure increases the ion conductivity of the positive electrode sheet itself, reduces the amount of electrolyte, and is assembled into a semi-solid battery, thereby improving the safety performance of the battery.

[0009] There are still some problems in the dry cathode process in the existing technology that need to be solved urgently, including: (1) In the existing dry electrode process, no solvent is used during the processing, and it is difficult to achieve uniform dispersion of the conductive agent and the binder in the cathode powder. Under this condition, the binder is further fibrillated, which will cause the binder to be locally fibrillated too much or too little in the powder, resulting in insufficient binder fibrillation, insufficient electrode membrane strength, poor film forming properties, and uneven distribution of the conductive agent, resulting in increased surface resistance and weak strength of the electrode membrane, which in turn affects the electrical properties of the electrode membrane. It is necessary to use higher performance fibrillation equipment and mixing equipment; (2) The fibrillation process of polytetrafluoroethylene (PTFE) is very sensitive to temperature and shear force, and it is difficult to accurately control the formation of a uniform self-supporting film; (3) Although the existing dry process can effectively control the thickness and uniformity of the electrode, it cannot simultaneously solve the difficult problems of long electron and ion transmission paths and slow conduction in thick electrodes, resulting in excessive polarization of the electrode sheet and inability to fully exert the electrochemical properties of the electrode material. (4) The existing dry process prepares the electrode membrane by hot rolling of the mixed powder, and then composites it with carbon-coated aluminum foil by hot rolling. However, due to the poor adhesion between the electrode membrane and the current collector, it leads to large interface impedance and even membrane peeling. The solutions in the existing technology can only solve a single problem from a certain aspect, but cannot solve all the above difficulties simultaneously. Summary of the invention

[0010] The purpose of this application is to provide a dry-process composite positive electrode plate and a preparation method thereof in response to the shortcomings of the existing dry-process positive electrode technology. The preparation method simultaneously solves the key problems faced by the practical application of the dry process through the coordination of multiple strategies such as preparation process optimization, equipment selection, electrode structure design and array-type through-hole carbon-coated aluminum foil development, and can prepare high-performance and high-load composite positive electrode plates. While preparing high-load electrodes, it simultaneously ensures the rapid transmission of ions and electrons and the high-strength bonding between the plate and the current collector, thereby fully exerting the electrochemical properties of the positive electrode material.

[0011] The technical solution of the present application is to provide a method for preparing a high-load dry composite positive electrode sheet, the method comprising:

[0012] Step 1, mixing a conductive agent, an oxide solid electrolyte and a positive electrode active material at a high speed to obtain a first powder, wherein the oxide solid electrolyte includes nanoparticles and micron particles;

[0013] Step 2, mixing the binder and the first powder at a low speed under low temperature conditions to obtain a second powder;

[0014] Step 3, pre-fiberizing and heat-insulating the second powder;

[0015] Step 4, adding the pre-fiberized second powder into a supersonic airflow mill, mixing the second powder with a supersonic airflow to fully fiberize the binder and uniformly disperse the other component materials to obtain a third powder;

[0016] Step 5, performing multi-stage hot roller pressing on the third powder to form an electrode membrane;

[0017] Step 6, rolling and compounding the carbon-coated aluminum foil current collector with an array through-hole structure and the electrode membrane to obtain a positive electrode sheet.

[0018] Furthermore, the particle size of nanoparticles ranges from 100 to 600 nm, and the particle size of microparticles ranges from 1 to 5 m, the mixing ratio of nanoparticles to microparticles ranges from 5:1 to 1:1.

[0019] Furthermore, the conductive agent is selected from one or more of carbon nanotubes and carbon nanofibers.

[0020] Furthermore, in step 1, the speed range of high-speed mixing is set to 5000-10000 r / min, and the mixing time is set to 30-300 min.

[0021] Furthermore, the oxide solid electrolyte is selected from one or more of a perovskite oxide solid electrolyte, a garnet oxide solid electrolyte, and a NASICON oxide solid electrolyte.

[0022] Furthermore, in step 2, the rotation speed range of the low-speed mixing is set to 200-800 r / min, the mixing time is set to 10-60 min, and the low temperature range is set to 0-10°C.

[0023] Furthermore, the temperature range of the pre-fiberization insulation is set to 90-200° C., and the insulation time is 2-10 hours.

[0024] Furthermore, the supersonic air flow velocity is greater than 300 m / s; and the temperature of the hot roller pressing is set to 150-250°C.

[0025] Furthermore, the content of the positive electrode active material is 80-96wt%, the content of the oxide solid electrolyte is 1-10wt%, the content of the conductive agent is 1-5wt%, and the content of the binder is 2-5wt%.

[0026] The technical solution of the present application also provides a high-load dry composite positive electrode plate, which includes: an electrode membrane and an array-type through-hole carbon-coated aluminum foil current collector, the electrode membrane is composited on one side of the array-type through-hole carbon-coated aluminum foil current collector, or the electrode membrane is composited on both sides of the array-type through-hole carbon-coated aluminum foil current collector, wherein the array-type through-hole carbon-coated aluminum foil current collector is provided with regularly arranged tiny through holes;

[0027] The electrode membrane includes a network structure formed by a binder, and a positive electrode active material, an oxide solid electrolyte and a conductive agent that are uniformly dispersed and tightly bonded in the network structure, wherein the oxide solid electrolyte and the conductive agent form a uniformly dispersed coating layer on the surface of the positive electrode active material particles, the conductive agent is selected from one or more of carbon nanotubes and carbon nanofibers, and the conductive agents overlap each other and form a continuous conductive network inside the electrode membrane.

[0028] The beneficial effects of this application are:

[0029] First, the technical solution of the present application introduces a highly conductive carbon material with a high aspect ratio and a highly conductive oxide solid electrolyte with different particle sizes; wherein the oxide solid electrolyte includes nanoparticles and micron particles, and the particles of the two different particle sizes are mixed in a preset ratio. During the preparation of the electrode membrane, the nanoparticles with small sizes can be more easily and tightly wrapped on the surface of the positive electrode active material particles, while the micron particles with large sizes can shorten the ion transmission path, reduce the number of particle interfaces, and are more conducive to the rapid transmission of lithium ions inside the electrode sheet, thereby improving the electrochemical performance; during the preparation process, the highly conductive carbon material with a high aspect ratio can be uniformly wrapped on the surface of the positive electrode active material particles together with the oxide solid electrolyte, and overlap each other to form a continuous conductive network, which is conducive to the rapid transmission of electrons; the conductive carbon material and the oxide solid electrolyte with different particle sizes can construct an efficient and continuous ion and electron transmission network inside the thick electrode sheet, reduce the polarization of the electrode sheet, solve the problem of long electron and ion transmission paths and slow conduction in the thick electrode, and improve the battery rate charge and discharge performance and the specific capacity of the active material.

[0030] Second, the technical solution in this application solves the problem of poor adhesion between the dry electrode membrane and the current collector interface and easy film removal. Different from the existing technical solution, the carbon-coated aluminum foil current collector used is processed by physical or chemical methods to form a regularly arranged tiny through holes to form an array structure, increase the contact area between the current collector and the electrode material and the roughness of the current collector surface, improve the adhesion and stability between the electrode membrane and the current collector, avoid the problem of falling off during charging and discharging, reduce the interface resistance, reduce the internal resistance of the battery, and reduce the polarization problem of the pole piece, thereby improving the battery's rate charging and discharging performance and cycle stability. The through-hole structure helps the electrolyte to quickly infiltrate and penetrate deeper into the thick electrode, improve the contact between the electrolyte and the electrode, and help improve the battery's charging and discharging performance. In addition, after the through-hole carbon-coated aluminum foil is processed by pore making, the weight of the current collector is greatly reduced, which can effectively improve the battery's energy density.

[0031] Third, the technical solution in this application has developed the technology of step-by-step mixing, pre-fiberization and strong shear mixing using supersonic airflow, mixing other component materials under high-speed conditions, and then mixing the binder under low-temperature and low-speed conditions to avoid uneven powder mixing due to premature fiberization of the binder, affecting the electrochemical performance and uniformity of the electrode membrane; adding a pre-fiberization step before the fiberization process to ensure that the binder can be fully fiberized in the subsequent process to improve the strength of the electrode membrane; using supersonic airflow to shear and mix the pre-fiberized powder, so that the binder is fully fiberized, and at the same time, the agglomerates of the conductive agent and the solid electrolyte are crushed by strong shear force to improve the dispersion effect of each component material, so that the conductive agent and the solid electrolyte form a uniformly dispersed coating on the surface of the positive electrode active material, and the positive electrode active material with the coating is more uniformly and tightly embedded in the binder fiber structure. The technical solution in this application can solve the problems of insufficient fibrillation and uneven mixing of the component materials in the prior art, and the prepared electrode membrane has high strength, low internal resistance and good film forming properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The advantages of the above and / or additional aspects of the present application will become apparent and easily understood in the description of the embodiments in conjunction with the following drawings, in which:

[0033] Figure 1 is a schematic flow chart of a method for preparing a high-load dry composite positive electrode sheet according to an embodiment of the present application;

[0034] Figure 2 are cross-sectional SEM images of the electrode membrane prepared in Example 1 and a cross-sectional SEM image of the electrode membrane prepared in Comparative Example 1;

[0035] Figure 3 is a cross-sectional SEM image of the electrode membrane prepared in Example 1 and its partial enlarged image;

[0036] Figure 4 is a capacity-voltage curve diagram of the electrode membrane prepared in Example 1 and the electrode membrane prepared in Comparative Example 1;

[0037] Figure 5 1 is a graph showing the specific capacity-voltage curves of the electrode membrane prepared in Example 1 and the electrode membrane prepared in Comparative Example 1;

[0038] Figure 6 is the capacity-voltage curve of the positive electrode sheet under different loading amounts prepared in Example 1;

[0039] Figure 7 It is the cycle retention rate curve of the electrode membrane prepared in Example 1 and the electrode membrane prepared in Comparative Example 1. DETAILED DESCRIPTION

[0040] In order to more clearly understand the above-mentioned purposes, features and advantages of the present application, the present application is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

[0041] In the following description, many specific details are elaborated to facilitate a full understanding of the present application. However, the present application may also be implemented in other ways different from those described herein. Therefore, the protection scope of the present application is not limited to the specific embodiments disclosed below.

[0042] like Figure 1 As shown, this embodiment provides a method for preparing a high-load dry composite positive electrode sheet, the preparation method comprising:

[0043] Step 1, adding the conductive agent, oxide solid electrolyte, and positive electrode active material into a high-speed dispersing device according to a preset ratio, and performing shearing and dispersion (i.e., a mixing process) under high speed and room temperature conditions to obtain a uniformly mixed first powder, wherein the powder particles of the oxide solid electrolyte include nanoparticles and micron particles, and the nanoparticles and micron particles are mixed in a certain ratio.

[0044] Preferably, the high-speed dispersing equipment adopts a powerful mixer. The high shear force of the powerful mixer can fully break up and disperse the conductive agent and solid electrolyte agglomerates, and the high-speed dispersing effect of the powerful mixer can make the conductive agent, solid electrolyte and active material evenly mixed. The speed range of the powerful mixer is set to 5000-10000r / min, the mixing time is set to 30-300min, and the mixing temperature is set to room temperature (room temperature is about 20°C to 25°C).

[0045] Step 2: Add the binder in a preset proportion to a high-speed dispersing device, shear and disperse the binder and the first powder under low speed and low temperature conditions to obtain a uniformly mixed second powder.

[0046] Preferably, the speed of the powerful mixer is reduced, the speed range is set to 200-800r / min, the stirring time is set to 10-60min, and the smaller shear force of the powerful mixer is used to achieve uniform dispersion of the binder in the first powder. At the same time, the temperature of the stirring tank is reduced to control the temperature within the range of 0-10°C. Reducing the speed of the powerful mixer and the temperature of the stirring tank can avoid premature fiberization of the binder in this process. Since the binder is highly sensitive to temperature and shear force, the binder is prone to fiberization at room temperature. Early fiberization will make it difficult to disperse evenly in the first powder, resulting in excessive or insufficient local binder, which ultimately affects the strength of the electrode membrane. Therefore, in step 2, it is necessary to reduce the speed of the powerful mixer and the temperature of the stirring tank to ensure that the binder is relatively evenly mixed between the positive electrode active material, the oxide solid electrolyte and the conductive agent under low temperature and low speed conditions.

[0047] Step 3: placing the second powder in a high-temperature oven, and utilizing the high sensitivity of the binder to temperature to pre-fiberize and keep the binder warm, so that it can be fully fiberized during the subsequent shearing and hot rolling process.

[0048] Preferably, the second powder is placed in a high-temperature oven for pre-fiberization and heat preservation, the heat preservation temperature range is set to 90-200°C, and the heat preservation time is set to 2-10h. The second powder obtained by mixing under low speed and low temperature conditions cannot maintain sufficient fluffiness due to the lower surface temperature. Directly performing the fiberization process will result in insufficient fiberization, causing the binder to break and fall off during subsequent rolling. Therefore, the second powder needs to be pre-fiberized and heat-insulated before the fiberization process, so that the binder crystals in the second powder are transformed into a soft and fluffy state, and the binder after pre-fiberization and heat preservation can be fully fiberized.

[0049] Step 4: Add the pre-fiberized second powder to a supersonic airflow pulverizer, use supersonic airflow to shear and disperse the second powder, so that the binder is fully fiberized to form a fluffy binder fiber structure, and at the same time, the secondary agglomerates of the conductive agent and the solid electrolyte are fully crushed and dispersed, and a uniformly dispersed coating layer is formed on the surface of the positive electrode active material. The positive electrode active material with the coating layer formed on the surface is uniformly embedded in the binder fiber structure to obtain a third powder.

[0050] Preferably, the fiberization process of the binder adopts a supersonic airflow pulverizer, which generates a supersonic airflow through an internal nozzle, and the supersonic airflow speed is greater than 300m / s. The pre-fiberized mixed powder material is added to the supersonic airflow pulverizer, and the compressed air in the supersonic airflow pulverizer forms a supersonic airflow after passing through the internal nozzle and is injected into the pulverizing chamber. Under the action of the supersonic airflow, the second powder is fluidized and converges at the intersection of the jet airflows of several nozzles, resulting in violent collision, friction and shearing. In this process, the secondary agglomerates of the conductive agent and the solid electrolyte are once again fully broken and dispersed, and a uniformly dispersed coating layer is formed on the surface of the positive electrode active material particles, thereby forming a good conductive and ion-conducting network; at the same time, the strong shear force of the supersonic airflow can fully fiberize the uniformly dispersed binder in the second powder to obtain a fluffy binder fiber structure, which can incorporate well-dispersed positive electrode active materials coated with conductive agents and solid electrolytes.

[0051] Step 5: The obtained third powder is transferred to a multi-stage hot rolling device and subjected to multiple hot rolling processes so that the binder fibers overlap and extrude each other to form a network structure, which wraps and bonds other materials in the third powder to form a self-supporting (referring to the property of being able to independently maintain its shape and structural integrity without relying on external support or substrate) electrode membrane with uniform thickness.

[0052] Preferably, the temperature of the hot rolling is set to 150-250°C. In step 5, the fluffy third powder is subjected to multiple hot rolling forming processes, and then hot pressing shaping, trimming and winding are performed to complete the entire hot pressing forming process. In this process, the operating temperature of the heating roller is set within the range of 150-250°C to ensure that the binder can be fully fiberized under the action of rolling and high temperature, so that the fibers overlap, squeeze and move with each other, and finally form a continuous binder fiber network, which can ensure the mechanical strength of the electrode diaphragm. In the process of step 5, the thickness of the electrode diaphragm can be precisely controlled by controlling the roller gap and pressure of the multi-stage rollers.

[0053] Step 6, rolling-compounding the array-type through-hole carbon-coated aluminum foil current collector treated by physical or chemical methods with the electrode membrane to obtain a high-load composite positive electrode sheet.

[0054] Preferably, the preset thickness of the composite positive electrode sheet is 30-500 μm, wherein the compaction density of the composite positive electrode sheet is related to the positive electrode material used. Taking NCM811 as an example, the preset range of the compaction density of the sheet is 2.8-3.8 g / cm 3During the manufacturing process, the thickness and compaction density can be selected according to actual needs. In addition, the electrode membrane and the current collector can be single-sided or double-sided composite according to actual application requirements, that is, the electrode membrane is composited on one side of the current collector, or the electrode membrane is composited on both sides of the current collector.

[0055] The current collector of the positive electrode sheet is a carbon-coated aluminum foil current collector that has been pore-formed. The carbon-coated aluminum foil current collector that has been pore-formed is different from the general carbon-coated aluminum foil and aluminum foil current collector. After its surface is treated by physical or chemical methods, an array of tiny through-hole structures is formed on the current collector. This through-hole structure can increase the roughness of the current collector surface, effectively improve the adhesion between the electrode membrane and the current collector interface, reduce the interface impedance, and is not easy to remove the membrane. At the same time, it can also reduce the weight of the current collector, reduce the internal resistance of the battery, and improve the energy density of the battery; Among them, the carbon-coated aluminum foil current collector after pore-formation treatment The array-type through-hole structure on the surface can improve the performance of the current collector. Specifically, the through-hole structure can serve as an anchor point for the electrode membrane, improve the adhesion between the electrode membrane and the current collector, and avoid falling off during the battery charging and discharging process. The through-hole structure increases the specific surface area of ​​the current collector, provides more active sites for electrochemical reactions, and allows more electrolyte to penetrate deeply into the electrode membrane, improving the contact between the electrolyte and the electrode. If double-sided composite is used, the through-hole structure can connect the electrode membranes on both sides of the current collector, which is more conducive to the transmission of electrons and ions. In addition, in step 6, the compaction of the composite positive electrode sheet can be controlled by adjusting the roller gap width and the roller pressure.

[0056] In this embodiment, the prepared electrode membrane includes a positive electrode active material, an oxide solid electrolyte, a conductive agent and a binder. During the preparation process, the positive electrode active material, the oxide solid electrolyte, the conductive agent and the binder are mixed according to a preset ratio, wherein the content of the positive electrode active material is 80-96wt%, the content of the oxide solid electrolyte is 1-10wt%, the content of the conductive agent is 1-5wt%, and the content of the binder is 2-5wt%.

[0057] The positive electrode active material can be selected from doped positive electrode active materials, undoped positive electrode active materials or coated modified positive electrode active materials; preferably, the positive electrode active material can be selected from lithium nickel cobalt manganese oxide (LiNi x Co y Mn 1-x-y O2), lithium nickel cobalt aluminum oxide (LiNi x Co y Al 1-x-y O2), lithium iron phosphate (LiFePO4), lithium iron manganese phosphate (LiMn x Fe 1-xPO4), lithium manganese oxide (LiMnO2) and lithium cobalt oxide (LiCoO2). In this embodiment, the type of positive electrode active material is not limited, and the positive electrode active materials commonly used in the art are applicable.

[0058] The oxide solid electrolyte is selected from one or more of perovskite oxide solid electrolytes, garnet oxide solid electrolytes, and NASICON oxide solid electrolytes; preferably, the perovskite oxide solid electrolyte is selected from lithium lanthanum titanium oxide; the garnet oxide solid electrolyte is selected from one or more of lithium lanthanum zirconium oxide, niobium-doped lithium lanthanum zirconium oxide, tantalum-doped lithium lanthanum zirconium oxide, and niobium-tantalum dual-doped lithium lanthanum zirconium oxide; the NASICON oxide solid electrolyte is selected from one or more of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, and lithium yttrium titanium phosphate.

[0059] Oxidized solid electrolyte powder particles are divided into two types, including micron particles and nanoparticles. Preferably, the particle size range of micron particles is 1-5μm, the particle size range of nanoparticles is 100-600nm, and the mixing ratio of nanoparticles and micron particles is 5:1-1:1. The oxide solid electrolyte particles using micron-sized particles and nano-sized particles can make the small nanoparticles tightly wrapped on the surface of the positive electrode active material during the manufacturing process, and the large micron particles can shorten the ion transmission path and reduce the number of particle interfaces, which is more conducive to the rapid transmission of ions inside the electrode sheet and improves the electrochemical performance of the electrode membrane.

[0060] The conductive agent is a conductive carbon material with high conductivity and high aspect ratio (the aspect ratio refers to the ratio of the length of the material to the diameter, which is an important parameter for measuring the material morphology). Preferably, the conductive carbon material is one or two of carbon nanotubes and carbon nanofibers. The conductive carbon material with high aspect ratio and high conductivity can be evenly wrapped on the surface of the positive electrode active material, and overlap with each other to build a continuous conductive network, which can enable electrons to be quickly transmitted inside the thick electrode plate.

[0061] The binder is at least one selected from polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP), polyacrylic acid (PAA), polyvinyl alcohol (PVA) and polyacrylonitrile (PAN), preferably polytetrafluoroethylene (PTFE).

[0062] This embodiment also provides a high-load dry composite positive electrode plate, which includes an electrode membrane and an array-type through-hole carbon-coated current collector that has been subjected to a pore-forming treatment, wherein the electrode membrane is made by the preparation method of steps 1 to 5 above, and the current collector adopts an array-type through-hole carbon-coated aluminum foil current collector that has been subjected to a pore-forming treatment.

[0063] Example 1:

[0064] Four raw materials, namely, lithium nickel cobalt manganese oxide (NCM811), conductive carbon nanotubes (CNT), solid electrolyte lithium aluminum titanium phosphate (LATP) and binder polytetrafluoroethylene (PTFE), were weighed according to a mass percentage of 93:2:3:2, wherein LATP is composed of nano-sized and micron-sized particles, and the ratio of nanoparticles to micron particles is 2:1; a through-hole carbon-coated aluminum foil is used as the current collector.

[0065] First, add the three raw materials of NCM811, CNT and LATP into a powerful mixer, stir at a speed of 8000r / min for 60min at room temperature, and mix the powders evenly to obtain the first powder. Pre-lower the temperature of the stirring tank of the powerful mixer to 5°C, add PTFE binder into the powerful mixer, and stir at a lower speed of 500r / min for 20min to ensure that PTFE is evenly dispersed in the first powder to form the second powder. Take the second powder out of the stirring tank and place it in a high-temperature oven. The oven temperature is set to 150°C and kept warm for 4h to pre-fiberize the binder and achieve the transformation of the crystal form, which is conducive to the subsequent full fiberization. Then add the second powder that has been pre-fiberized and kept warm to the supersonic airflow pulverizer. By controlling the compressed air flow rate and pressure, ensure that the air flow rate exceeds 300m / s, achieve full dispersion of each component material and full fiberization of the binder, and obtain a fluffy third powder. Then, the fluffy third powder is transferred to the multi-stage hot rolling equipment through the powder metering and conveying device. The rolling temperature is set to 200°C. After multiple hot rolling, it is rolled up to obtain a self-supporting No. 1 electrode membrane. Finally, the No. 1 electrode membrane is hot-pressed and composited to the through-hole carbon-coated aluminum foil through the hot rolling equipment to obtain the No. 1 positive electrode sheet.

[0066] Example 2:

[0067] Four raw materials, namely, lithium nickel cobalt manganese oxide (NCM811), conductive carbon nanotubes (CNT), solid electrolyte (LATP) and binder polytetrafluoroethylene (PTFE), were weighed in a mass percentage of 91:2:5:2, wherein LATP was composed of nano-sized and micron-sized particles, and the ratio of nanoparticles to micron particles was 3:2; a through-hole carbon-coated aluminum foil was used as the current collector.

[0068] First, add the three raw materials of NCM811, CNT and LATP into a powerful mixer, stir at a speed of 10000r / min for 30min at room temperature, and mix the powders evenly to obtain the first powder. Pre-lower the temperature of the stirring tank to 5°C, add PTFE binder into the mixer, and stir at a lower speed of 500r / min for 20min to ensure that PTFE is evenly dispersed in the first powder to form the second powder. Take the second powder out of the stirring tank and place it in a high-temperature oven at 150°C for 4h to pre-fiberize the binder and achieve the transformation of the crystal form, which is conducive to the subsequent full fiberization. Then add the second powder that has been pre-fiberized and insulated into the supersonic airflow pulverizer. By controlling the compressed air flow rate and pressure, ensure that the air flow rate exceeds 300m / s, achieve full dispersion of each component material and full fiberization of the binder, and obtain the third powder in a fluffy state. Then, the fluffy third powder is transferred to the multi-stage hot rolling equipment through the powder metering and conveying device. The rolling temperature is 200°C. After multiple hot rolling, it is rolled up to obtain a self-supporting No. 2 electrode membrane. Finally, the No. 2 electrode membrane is hot-pressed and composited to the through-hole carbon-coated aluminum foil through the hot rolling equipment to obtain the No. 2 positive electrode sheet.

[0069] Example 3:

[0070] Four raw materials, namely, lithium nickel cobalt manganese oxide (NCM811), conductive carbon nanotubes (CNT), solid electrolyte (LATP) and binder polytetrafluoroethylene (PTFE), were weighed in a mass percentage of 91:3:3:3, wherein LATP was composed of nano-sized and micron-sized particles, and the ratio of nanoparticles to micron particles was 2:1; a through-hole carbon-coated aluminum foil was used as the current collector.

[0071] First, add the three raw materials of NCM811, CNT and LATP into a powerful mixer, stir at a speed of 8000r / min for 30 minutes at room temperature, and mix the powders evenly to obtain the first powder. Pre-lower the temperature of the stirring tank to 5°C, add PTFE binder into the mixer, and stir at a lower speed of 600r / min for 30 minutes to ensure that PTFE is evenly dispersed in the first powder to form the second powder. Take the second powder out of the stirring tank and place it in a high-temperature oven at 160°C for 4 hours to pre-fiberize the binder and achieve the transformation of the crystal form, which is conducive to the subsequent full fiberization. Then add the second powder that has been pre-fiberized and insulated into the supersonic airflow pulverizer. By controlling the compressed air flow rate and pressure, ensure that the air flow rate exceeds 300m / s, achieve full dispersion of each component material and full fiberization of the binder, and obtain the third powder in a fluffy state. Then, the fluffy third powder is transferred to the multi-stage hot rolling equipment through the powder metering and conveying device. The rolling temperature is 200°C. After multiple hot rolling, it is rolled up to obtain a self-supporting No. 3 electrode membrane. Finally, the No. 3 electrode membrane is hot-pressed and composited to the through-hole carbon-coated aluminum foil through the hot rolling equipment to obtain the No. 3 positive electrode sheet.

[0072] Example 4:

[0073] Four raw materials, namely, lithium nickel cobalt manganese oxide (NCM811), conductive carbon nanotubes (CNT), solid electrolyte (LATP) and binder polytetrafluoroethylene (PTFE), were weighed in a mass percentage of 91:2:3:4, wherein LATP was composed of nano-sized and micron-sized particles, and the ratio of nanoparticles to micron particles was 2:1; a through-hole carbon-coated aluminum foil was used as the current collector.

[0074] First, add the three raw materials of NCM811, CNT and LATP into a powerful mixer, stir at a speed of 8000r / min for 60min at room temperature, and mix the powders evenly to obtain the first powder. Pre-lower the temperature of the stirring tank to 5°C, add PTFE binder into the mixer, and stir at a lower speed of 600r / min for 40min to ensure that PTFE is evenly dispersed in the first powder to form the second powder. Take the second powder out of the stirring tank and place it in a high-temperature oven at 150°C for 4h to pre-fiberize the binder and achieve the transformation of the crystal form, which is conducive to the subsequent full fiberization. Then add the second powder that has been pre-fiberized and insulated into the supersonic airflow pulverizer. By controlling the compressed air flow rate and pressure, ensure that the air flow rate exceeds 300m / s, achieve full dispersion of each component material and full fiberization of the binder, and obtain the third powder in a fluffy state. Then, the fluffy third powder body is transferred to the multi-stage hot rolling equipment through the powder metering and conveying device. The rolling temperature is 200°C. After multiple hot rolling, it is rolled up to obtain a self-supporting No. 4 electrode membrane. Finally, the No. 4 electrode membrane is hot-pressed and composited to the through-hole carbon-coated aluminum foil through the hot rolling equipment to obtain the No. 4 positive electrode sheet.

[0075] Comparative Example 1:

[0076] Four raw materials, namely, lithium nickel cobalt manganese oxide (NCM811), carbon nanotubes, solid electrolyte (LATP) and binder polytetrafluoroethylene (PTFE), were weighed in a mass percentage of 93:2:3:2. LATP was composed of nano-sized and micron-sized particles, and the ratio of nanoparticles to micron particles was 2:1. Conventional carbon-coated aluminum foil was used as the current collector.

[0077] These raw materials were added to a powerful mixer and stirred at a speed of 10,000 r / min for 60 minutes at room temperature. The obtained powder was transferred to a multi-stage hot roller pressing device through a powder metering conveyor. The rolling temperature was 200°C. After multiple hot roller pressings, the self-supporting No. 5 electrode membrane was rolled up. The No. 5 electrode membrane was hot-pressed and composited to a conventional carbon-coated aluminum foil through a hot roller pressing device to obtain a No. 5 positive electrode sheet.

[0078] Comparative Example 2:

[0079] Four raw materials, namely, lithium nickel cobalt manganese oxide (NCM811), conductive carbon nanotubes (CNT), solid electrolyte (LATP) and binder polytetrafluoroethylene (PTFE), were weighed in a mass percentage of 93:2:3:2, wherein LATP was a micron-sized powder and conventional carbon-coated aluminum foil was used as the current collector.

[0080] First, add the three raw materials of NCM811, CNT and LATP into a powerful mixer, stir at a speed of 8000r / min for 60min at room temperature, and mix the powders evenly to obtain the first powder. Pre-lower the temperature of the stirring tank to 5°C, add PTFE binder into the mixer, and stir at a lower speed of 500r / min for 20min to ensure that PTFE is evenly dispersed in the first powder to form the second powder. Take the second powder out of the stirring tank and place it in a high-temperature oven at 150°C for 4h to pre-fiberize the binder and achieve the transformation of the crystal form, which is conducive to the subsequent full fiberization. Then add the second powder after pre-fiberization and insulation into the supersonic airflow pulverizer. By controlling the compressed air flow rate and pressure, ensure that the airflow speed exceeds 300m / s, achieve full dispersion of each component material and full fiberization of bonding, and obtain the third powder in a fluffy state. Then, the fluffy third powder is transferred to the multi-stage hot rolling equipment through the powder metering and conveying device. The rolling temperature is 200°C. After multiple hot rolling, it is rolled up to obtain a self-supporting No. 6 electrode membrane. Finally, the No. 6 electrode membrane is hot-pressed and composited to the conventional carbon-coated aluminum foil through the hot rolling equipment to obtain the No. 6 positive electrode sheet.

[0081] Comparative Example 3:

[0082] Four raw materials, namely, lithium nickel cobalt manganese oxide (NCM811), conductive carbon SP, solid electrolyte (LATP) and binder polytetrafluoroethylene (PTFE), were weighed in a mass percentage of 93:2:3:2. LATP was composed of nano-sized and micron-sized particles, and the ratio of nanoparticles to micron particles was 2:1. Conventional carbon-coated aluminum foil was used as the current collector.

[0083] First, add the three raw materials of NCM811, SP and LATP into a powerful mixer, stir at a speed of 8000r / min for 60min at room temperature, and mix the powders evenly to obtain the first powder. Pre-lower the temperature of the stirring tank to 5°C, add PTFE binder into the mixer, and stir at a lower speed of 500r / min for 20min to ensure that PTFE is evenly dispersed in the first powder to form the second powder. Take the second powder out of the stirring tank and place it in a high-temperature oven at 150°C for 4h to pre-fiberize the binder and achieve the transformation of the crystal form, which is conducive to the subsequent full fiberization. Then add the second powder after pre-fiberization and insulation into the supersonic airflow pulverizer, and control the compressed air flow rate and pressure to ensure that the airflow speed exceeds 300m / s, so as to achieve full dispersion of each component material and full fiberization of the binder, and obtain the third powder in a fluffy state. Then, the fluffy third powder is transferred to the multi-stage hot rolling equipment through the powder metering and conveying device. The rolling temperature is 200°C. After multiple hot rolling, it is rolled up to obtain a self-supporting No. 7 electrode membrane. Finally, the No. 7 electrode membrane is hot-pressed and composited to the conventional carbon-coated aluminum foil through the hot rolling equipment to obtain the No. 7 positive electrode sheet.

[0084] Comparative Example 4:

[0085] Four raw materials, namely, lithium nickel cobalt manganese oxide (NCM811), carbon nanotubes, solid electrolyte (LATP) and binder polytetrafluoroethylene (PTFE), were weighed in a mass percentage of 93:2:3:2. LATP was composed of nano-sized and micron-sized particles, and the ratio of nanoparticles to micron particles was 2:1. Conventional carbon-coated aluminum foil was used as the current collector.

[0086] First, add these raw materials to a high-efficiency mixer and stir at a speed of 8000r / min for 60 minutes at room temperature. Add the obtained powder to the supersonic airflow pulverizer, and control the compressed air flow rate and pressure to ensure that the airflow speed exceeds 300m / s to obtain a fluffy powder. Finally, the fluffy powder is transferred to the multi-stage hot rolling equipment through the powder metering and conveying device. The rolling temperature is 200℃. After multiple hot rolling, it is rolled up to obtain a self-supporting No. 8 electrode diaphragm. The No. 8 electrode diaphragm is hot-pressed and composited to a conventional carbon-coated aluminum foil through a hot rolling equipment to obtain a No. 8 positive electrode sheet.

[0087] The different positive electrode sheets prepared in the above examples 1-4 and comparative examples 1-4 were tested, and the test contents are as follows:

[0088] Electrode piece resistance test: Use a electrode piece resistance meter to test. Under the environment of room temperature of 25℃ and dew point of -40℃ (used to indicate air humidity), place the prepared positive electrode piece on the table of the resistance meter to make its surface flat. Adjust the pressure gauge to fix the test electrode piece to ensure good contact between the probe and the electrode piece, and obtain the resistance values ​​of positive electrode pieces No. 1 to No. 8 in turn.

[0089] Peel strength test: Use a peel force tester to test. At room temperature of 25°C and dew point of -40°C, adhere one side of the current collector of the prepared battery positive electrode sheet to the working panel with a test double-sided tape, and use a test tape to connect the surface of the electrode film and the peel force tester. Set the peel speed to 60mm / min and the peel angle to 180°. Test and record the peel forces of positive electrode sheets No. 1 to No. 8 in turn.

[0090] Electrochemical performance test: The prepared positive electrode sheet, metal lithium negative electrode sheet, separator and electrolyte were assembled to form eight different button batteries. The battery numbers correspond to the numbers of the positive electrode sheets used, which are No. 1 to No. 8 batteries. At 25°C, charge and discharge at a rate of 0.1C, and record the discharge specific capacity of No. 1 to No. 8 positive electrode sheets in turn; at 25°C, charge and discharge at a rate of 1C, and record the discharge specific capacity of No. 1 to No. 8 positive electrode sheets in turn (other rates, such as 2C or 3C, can also be selected according to actual conditions. The battery is charged and discharged at different rates. The purpose is to test the discharge capacity, discharge specific capacity and capacity retention rate of the battery at different rates); at 25°C, charge and discharge 100 times at a rate of 0.3C, record the battery capacity before and after the cycle of No. 1 to No. 8 batteries in turn, and calculate the capacity retention rate of No. 1 to No. 8 batteries.

[0091] The test results of different positive electrode sheets and their corresponding button batteries are shown in Table 1:

[0092] Table 1

[0093]

[0094] Examples 1-4 and Comparative Examples 2-3 use the method of the present invention to prepare positive electrode sheets, wherein the solid electrolyte in Comparative Example 2 is a single micron particle, the conductive agent in Comparative Example 3 is conductive carbon SP, and Comparative Examples 1 and Comparative Examples 4 use the prior art method to prepare positive electrode sheets.

[0095] It can be seen from the data in Table 1 that, under the condition that the multi-component materials are the same, the positive electrode sheet prepared by the method of the present invention has a lower internal resistance, a higher discharge specific capacity at different rates, and a higher capacity retention rate. For example, the resistance of the positive electrode sheets No. 1 to No. 4 in the table is lower than that of the positive electrode sheets No. 5 and No. 8, and the discharge specific capacity and capacity retention rate of the positive electrode sheets No. 1 to No. 4 are higher than those of the positive electrode sheets No. 5 and No. 8; when conductive carbon nanotubes are used as the conductive agent, the internal resistance of the positive electrode sheet is reduced, and the discharge specific capacity and capacity retention rate are higher. For example, the conductive agent of the positive electrode sheet No. 7 in the table is conductive carbon SP, and when other materials and conditions are the same, the positive electrode sheet No. 7 has a higher internal resistance than the positive electrode sheet No. 5 and No. 8. The electrode sheet resistance of the sheet is much greater than that of the positive electrode sheets No. 1 to No. 4, and the discharge specific capacity at a rate of 1C and the capacity retention rate after 100 cycles at a rate of 0.3C are both lower than those of the positive electrode sheets No. 1 to No. 4; when a powder composed of nanoparticles and micron particles in a certain proportion is used as a solid electrolyte, the internal resistance of the positive electrode sheet is reduced, and the discharge specific capacity and capacity retention rate are improved. For example, the solid electrolyte of the positive electrode sheet No. 6 in the table is a single micron particle. Under the same other materials and conditions, the electrode sheet resistance of the positive electrode sheet No. 6 is greater than that of the positive electrode sheets No. 1 to No. 4, and the discharge specific capacity and capacity retention rate are both lower than those of the positive electrode sheets No. 1 to No. 4. In the present invention, the positive electrode sheet is prepared by using a through-hole carbon-coated aluminum foil that has been pore-formed, which can improve the bonding force between the electrode membrane and the current collector. For example, the peel strength of the positive electrode sheets No. 1 to No. 4 in the table is much greater than the peel strength of the positive electrode sheets No. 5 to No. 8.

[0096] like Figure 2 As shown, Figure 2 (a) is a cross-sectional SEM (scanning electron microscope) image of the No. 1 electrode membrane prepared by the method of the present invention in Example 1. Figure 2 (b) is a cross-sectional SEM image of the No. 5 electrode membrane prepared by the prior art method in Comparative Example 1. After comparison, it can be clearly seen that in the No. 1 electrode membrane, the mixing uniformity of the multi-component materials is higher, and the fiberization of the binder is more sufficient. Combined with the data in Table 1, it can be seen that the electrode membrane prepared by the method of the present invention can achieve uniform mixing of multi-component materials and sufficient fiberization of the binder. The fully fiberized binder forms a three-dimensional network structure, and the particles of the remaining components are uniformly and tightly wrapped in the three-dimensional network to form a uniform electrode structure. The uniform electrode can reduce the electrode sheet resistance and reduce the polarization during the charge and discharge process. At the same time, it improves the mechanical strength and structural stability of the electrode membrane, which helps to improve the cycle stability of the electrode.

[0097] like Figure 3 As shown, Figure 3 (a) is a cross-sectional SEM image of the electrode membrane No. 1 prepared by the method of the present invention in Example 1. Figure 3 (b) in the equation is Figure 3From the partial enlarged view of (a), it can be seen that the internal materials of the electrode diaphragm are closely connected and evenly distributed.

[0098] like Figure 4 The capacity-voltage curve of No. 1 battery and No. 5 battery. Figure 5 The specific capacity-voltage curve of No. 1 battery and No. 5 battery. Figure 4 The comparison shows that under the same voltage range and electrode area, the No. 1 battery has a higher area capacity. Figure 5 By comparison, it was found that even at a higher surface loading, battery No. 1 had a higher discharge specific capacity, indicating that the positive electrode material has a higher capacity utilization.

[0099] like Figure 6 As shown in the figure, under different loads, the high-load composite positive electrode can charge and discharge normally, and the maximum area capacity is as high as 11mAh / cm 2 , which is 2~3 times the area capacity of wet coating, indicating that the efficient and continuous ion and electron transport network constructed inside the high-load composite positive electrode can solve the problems of long electron and ion transport paths and slow conduction in thick electrodes, and improve the battery rate charging and discharging performance and the specific capacity of active materials.

[0100] like Figure 7 As shown, after 100 cycles of charge and discharge at a rate of 0.3C, the capacity retention rate of the No. 1 battery is still higher than 90%, while after 100 cycles of charge and discharge at a rate of 0.3C, the capacity of the No. 5 battery drops below 90%. Compared with the No. 5 battery, the electrochemical performance of the No. 1 battery is better. It can be seen that the method of the present invention can reduce the polarization phenomenon and the structural change of the positive electrode material during the charge and discharge process, improve the cycle stability and safety of the battery, and enhance the electrochemical performance.

[0101] The high-load dry-process composite positive electrode sheet prepared by the method of steps 1 to 6 has high energy density, excellent cycle stability and good conductivity, and can be applied to liquid lithium-ion batteries, semi-solid lithium-ion batteries and other fields; wherein, the electrode membrane can be composited on one side of the array-type through-hole carbon-coated aluminum foil current collector to form a single-sided composite positive electrode sheet, or the electrode membrane can also be composited on both sides of the array-type through-hole carbon-coated aluminum foil current collector to form a double-sided composite positive electrode sheet.

[0102] Specifically, when applied to liquid lithium-ion batteries, the positive electrode sheet is cut into a suitable size and placed in a battery casing together with the negative electrode sheet, and the electrolyte is injected into the battery to fully infiltrate the positive and negative electrode sheets, so that a stable solid-liquid interface is formed between the positive electrode and the electrolyte, wherein the electrolyte exists between the positive and negative electrode sheets. When applied to semi-solid lithium-ion batteries, an electrolyte with a content of 5wt%-10wt% is usually injected, or the electrolyte is converted into a gel state by an in-situ curing process, so that a stable solid-liquid or solid-gel interface is formed between the positive electrode and the electrolyte, and a small amount of electrolyte or gel electrolyte exists between the positive and negative electrode sheets. The rest of the structure is the same as that of a liquid lithium-ion battery; the array-type through-hole carbon-coated aluminum foil current collector in the positive electrode sheet can not only help disperse the current and improve ion conduction, but also reduce the weight of the current collector, increase the energy density of the battery, and further enhance the conductivity, so that the electrode sheet can maintain good conductivity under high load conditions, thereby improving the overall performance of the battery.

[0103] The steps in this application can be adjusted in order, combined, and deleted according to actual needs.

[0104] The units in the device of the present application can be combined, divided and deleted according to actual needs.

[0105] Although the present application is disclosed in detail with reference to the accompanying drawings, it should be understood that these descriptions are merely exemplary and are not intended to limit the application of the present application. The scope of protection of the present application is defined by the appended claims and may include various modifications, alterations and equivalents made to the invention without departing from the scope and spirit of the present application.

Claims

1. A method for preparing a high-load dry composite positive electrode sheet, characterized in that: The method for preparing the high-load dry composite positive electrode plate comprises: Step 1, mixing a conductive agent, an oxide solid electrolyte and a positive electrode active material at a high speed to obtain a first powder, wherein the oxide solid electrolyte comprises nanoparticles and micron particles, the nanoparticles have a particle size range of 100-600 nm, and the micron particles have a particle size range of 1-5 m, the mixing ratio of the nanoparticles and the micron particles is in the range of 5:1 to 1:1, and the conductive agent is selected from one or more of carbon nanotubes and carbon nanofibers; Step 2, under low temperature conditions, mixing the binder and the first powder at a low speed to obtain a second powder, wherein the speed range of the low-speed mixing is set to 200-800 r / min, the low temperature range is set to 0-10° C., the mixing time is set to 10-60 min, and the binder is selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride hexafluoropropylene, polyacrylic acid, polyvinyl alcohol and polyacrylonitrile; Step 3, pre-fiberizing and heat-insulating the second powder, wherein the pre-fiberizing and heat-insulating temperature range is set to 90-200° C., and the heat-insulating time is 2-10 hours; Step 4, adding the second powder after pre-fiberization into a supersonic airflow pulverizer, mixing the second powder with a supersonic airflow, so that the binder is fully fiberized and other component materials are uniformly dispersed, to obtain a third powder, wherein the supersonic airflow velocity is greater than 300 m / s; Step 5, performing multi-stage hot rolling pressing on the third powder to form an electrode membrane; Step 6, rolling and compounding the carbon-coated aluminum foil current collector having an array through-hole structure and the electrode membrane to obtain a positive electrode sheet.

2. The method for preparing a high-load dry composite positive electrode sheet according to claim 1, characterized in that: In the step 1, the speed range of high-speed mixing is set to 5000-10000 r / min, and the mixing time is set to 30-300 min.

3. The method for preparing a high-load dry composite positive electrode sheet according to claim 1, characterized in that: The oxide solid electrolyte is selected from one or more of a perovskite oxide solid electrolyte, a garnet oxide solid electrolyte, and a NASICON oxide solid electrolyte.

4. The method for preparing a high-load dry composite positive electrode sheet according to claim 1, characterized in that: The temperature of the hot roller press is set at 150-250°C.

5. The method for preparing a high-load dry composite positive electrode sheet according to claim 1, characterized in that: The content of the positive electrode active material is 80-96wt%, the content of the oxide solid electrolyte is 1-10wt%, the content of the conductive agent is 1-5wt%, and the content of the binder is 2-5wt%.

6. A high-load dry-process composite positive electrode sheet prepared by the method for preparing a high-load dry-process composite positive electrode sheet according to any one of claims 1 to 5, characterized in that: The positive electrode sheet comprises an electrode membrane and an array-type through-hole carbon-coated aluminum foil current collector, wherein the electrode membrane is composited on one side of the array-type through-hole carbon-coated aluminum foil current collector, or the electrode membrane is composited on both sides of the array-type through-hole carbon-coated aluminum foil current collector, wherein the array-type through-hole carbon-coated aluminum foil current collector is provided with regularly arranged tiny through holes; The electrode membrane includes a network structure formed by a binder, and a positive electrode active material, an oxide solid electrolyte and a conductive agent that are uniformly dispersed and tightly bonded in the network structure, wherein the oxide solid electrolyte and the conductive agent form a uniformly dispersed coating layer on the surface of the positive electrode active material particles, the conductive agent is selected from one or more of carbon nanotubes and carbon nanofibers, and the conductive agents overlap each other and form a continuous conductive network inside the electrode membrane.

Citation Information

Patent Citations

  • Positive electrode material layer suitable for semi-solid-state batteries, its preparation method, positive electrode sheet and semi-solid-state battery

    CN112133923B

  • A dry electrode film, its preparation method and application

    CN113871566B

  • Dry-method electrode and preparation method thereof

    CN117154005A

  • Method for preparing electrode membrane of lithium ion battery by dry method

    CN115579458A

  • Collector material, and method of manufacturing the same

    JP2008283152A